TINJAUAN YURIDIS PERATURAN OTORITAS JASA KEUANGAN (POJK) NOMOR 77 TAHUN 2016 TENTANG LAYANAN PINJAMAN UANG BERBASIS TEKNOLOGI INFORMASI TERHADAP PERJANJIAN PINJAMAN UANG MELALUI FINANCIAL TECHNOLOGY (FINTECH) - MOHAMMAD ANTON SURYADI; M. Rizal Efendi (STIH Zainul Hasan Kraksaan Kraksaan, 2022)
Abstract The issuance of the Financial Services Authority Regulation (POJK) number 77 of 2016 as a form of regulation regarding information technology-based money loans. Financial Technology (Fintech) is the latest innovation in the financial sector which is the locomotive for the development of sophisticated technology. The results of this study indicate that (a) the agreement is valid if it follows Article 1320 of the Civil Code. In an online loan agreement, an agreement that occurs when the creditor / lender and debtor / loan recipient both fulfill their rights and obligations as business actors and consumers where both enter into a loan agreement and as long as the loan agreement does not harm both parties, the loan agreement online is considered legal, (b) a form of legal protection for the parties in an online loan agreement, is the arrangement of the rights and obligations of the parties, such as the rights and obligations of business actors to have the right to get payments from consumers for loans given and are also entitled to get protection against actions of consumers who have bad intentions in carrying out the agreement and the rights and obligations of consumers are regulated in article 4 of law number 8 of 1999. consumers are obliged to pay a certain amount of money for loans that have been ordered from creditors. This study uses a normative method or study, with the aim of knowing how the implementation and role of the Financial Services Authority Regulation number 77 of 2016 plays a role in protecting the rights of consumers and debtors, therefore researchers are interested in studying it in this study as a form of providing assistance. socialization about online loan agreements so that the public knows about the procedures for online loan agreements, as well as the rights and obligations for business actors and consumers. So that the formulation of the problem that will be discussed is How is an online loan agreement (credit)? and How is the Legal Protection in Online Money Loan Agreements? Keywords: Financial Services Authority, online loans, Law number 77 of 2016